W stronę szkoły wychowującej = Approaching the school which educates - Szołtysek, Adolf E. (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The reform, that has been entering our school system for some time now, requires revaluation of both teaching and education, also in the context of reaching the European standards. We are still facing the great challenges which should be answered by all people involved in Polish school system; especially by the professors at the universities, since they are the people who possess an unquestionable influence on the consciousness of our future educators.
Keywords: szkolnictwo; wychowanie